eCM 2011
DOI: 10.22203/ecm.v021a03
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ADAMTS5 and hyaluronidase in aggrecan degradation and release from OSM-stimulated cartilage

Abstract: The relative contribution of a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)4 and ADAMTS5 to aggrecan degradation under oncostatin M (OSM) stimulation, the role of the ancillary domains of the aggrecanases on their ability to cleave within the chondroitin sulfate (CS)-2 region, the role of hyaluronidases (HYAL) in stimulating aggrecan release in the absence of proteolysis, and the identity of the hyaluronidase involved in OSM-mediated cartilage breakdown were investigated. Bovine articu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 49 publications
5
23
0
Order By: Relevance
“…Our fi nding that OSM+IL-1 increased both ADAMTS4 and 5 mRNA expression is consistent with previous studies using bovine cartilage explants Blain et al, 2010;Durigova et al, 2011) and human primary chondrocytes . In addition, Koshy et al (Koshy et al, 2002) reported that OSM+IL-1 induced ADAMTS4 but not ADAMTS5 in T/C28a4 cells (Koshy et al, 2002).…”
Section: Signalling In Chondrocytessupporting
confidence: 93%
See 3 more Smart Citations
“…Our fi nding that OSM+IL-1 increased both ADAMTS4 and 5 mRNA expression is consistent with previous studies using bovine cartilage explants Blain et al, 2010;Durigova et al, 2011) and human primary chondrocytes . In addition, Koshy et al (Koshy et al, 2002) reported that OSM+IL-1 induced ADAMTS4 but not ADAMTS5 in T/C28a4 cells (Koshy et al, 2002).…”
Section: Signalling In Chondrocytessupporting
confidence: 93%
“…Our data show that although ADAMTS5 was more highly expressed than ADAMTS4, the OSM+IL-1-induced increases were far greater for ADAMTS4 gene expression compared to ADAMTS5 (830-fold vs. 40-fold). These data, in conjunction with previous fi ndings ( Koshy et al, 2002;Durigova et al, 2011), suggest that ADAMTS4 is the primary aggrecanase responsible for the synergistic action of OSM+IL-1 on aggrecan degradation. We have shown for the fi rst time that OSM+IL-1 induced up-regulation of ADAMTS4 and ADAMTS5 is, in part, mediated through PKR.…”
Section: Signalling In Chondrocytessupporting
confidence: 84%
See 2 more Smart Citations
“…haematopoiesis, neural and liver development and cell proliferation (Miyajima et al, 2000;Tanaka et al, 2003;Tanaka and Umesaki, 2003) and in rheumatoid arthritis (RA), OSM is associated with bone erosion, synovial inflammation and fibrosis, and cartilage degeneration (Sims and Walsh, 2010;Walker et al, 2010). The potential of OSM to degenerate cartilage and induce catabolic processes in chondrocytes was shown in different studies (Barksby et al, 2006;Durigova et al, 2011), although nothing is known about its effect on cartilage synthesis. In addition, OSM is known to synergise with catabolic cytokines such as IL-1 and TNFa in the induction of cartilage degeneration in vitro (Barksby et al, 2006;Catterall et al, 2001;Gilbert et al, 2012;Hui et al, 2001;Hui et al, 2003).…”
Section: Introductionmentioning
confidence: 99%